Waste-to-Energy Modeling via Digital Algorithms Based on Faith-Based Cleanliness and Education - Bambang Judi Bagiono; Nasirudin Nasirudin (PT. Student RIhlah Indonesia, 2026)
This research examines the integration of Islamic cleanliness principles into digital algorithm modeling as a conceptual foundation for ethical system design. In Islamic thought, cleanliness encompasses not only physical purity but also moral intention, cognitive clarity, and structural order, as articulated by Al-Ghazali. The objective of this study is to formulate a value-based digital algorithm framework grounded in these principles. The research employs a qualitative conceptual methodology through critical literature review of classical Islamic scholarship and contemporary digital modeling and algorithm studies published within the last decade. The results demonstrate that Islamic cleanliness principles can be systematically translated into algorithmic stages, including purified input selection, integrity-driven processing, and accountable output validation. The discussion indicates that this approach introduces an ethical and spiritual dimension absent from most conventional algorithmic models. The novelty of this study lies in its interdisciplinary synthesis of Islamic ethical philosophy and formal digital system modeling. The findings have important policy implications for ethical artificial intelligence, digital governance, and education systems, particularly in culturally and religiously contextualized environments. This research is significant as it provides an original conceptual contribution to the development of responsible and value-oriented digital transformation.